2003
DOI: 10.1088/0022-3727/36/12/307
|View full text |Cite
|
Sign up to set email alerts
|

Numerical study of the effect of gas temperature on the time for onset of particle nucleation in argon–silane low-pressure plasmas

Abstract: Particle nucleation in silane plasmas has attracted interest for the past decade, both due to the basic problems of plasma chemistry involved and the importance of silane plasmas for many applications. A better understanding of particle nucleation may facilitate the avoidance of undesirable particle contamination as well as enable the controlled production of nanoparticles for novel applications. While understanding of particle nucleation has significantly advanced over the past years, a number of questions ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
56
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 52 publications
1
56
0
Order By: Relevance
“…Finally, Warthesen et al 16 proposed a decreased gas density (at constant pressure) explaining the observed effect. Bhandarkar et al 17 showed in a comparisonal numerical study that-although present-none of these processes could adequately explain the observed delay. Those authors demonstrated that the temperature dependence of the Brownian diffusion coefficient was the most dominant factor in the nucleation delay in silane.…”
mentioning
confidence: 84%
See 2 more Smart Citations
“…Finally, Warthesen et al 16 proposed a decreased gas density (at constant pressure) explaining the observed effect. Bhandarkar et al 17 showed in a comparisonal numerical study that-although present-none of these processes could adequately explain the observed delay. Those authors demonstrated that the temperature dependence of the Brownian diffusion coefficient was the most dominant factor in the nucleation delay in silane.…”
mentioning
confidence: 84%
“…Those authors demonstrated that the temperature dependence of the Brownian diffusion coefficient was the most dominant factor in the nucleation delay in silane. 17 With respect to the gas temperature dependence of nanoparticles formation in silane based plasmas, some researchers have discussed processes in terms of diffusion times of protoparticles and their critical density necessary of coagulation onset. 18,19 For Ar/CH 4 discharges, the temperature dependence of the coagulation time has been studied experimentally.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To this end, one such task is the investigation of Si nanoparticles, which are often studied using plasma chemical reactors at low pressure (10 to 100 Pa), and radio frequency (RF) discharge in pure silane or gas mixtures such as Ar-SiH 4 and He-SiH 4 (see, for example, the book 1 ). Detailed experimental investigations of Si particle growth have been performed, [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] while theoretical studies of Si nanoparticle growth have also been carried out, developing both complex [19][20][21][22] and relatively simple [23][24][25][26][27][28] models. However, direct comparisons of experimental and theoretical results have not been shown in most cases.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, this must be the maximal rate of production of cluster-dimers. Detailed chemical analyses 20,21,30 have shown that SiH 3 -SiH 3 collisions do not lead to the formation of Si 2 H m dimer-radicals. These dimers can be obtained due to the SiH 2 radical.…”
mentioning
confidence: 99%